Pengaruh Terpaan Media Sosial Twitter @Ohmybeautybank Terhadap Perilaku Konsumtif Followers - Aldyssa, Wanda; Sary, Kezia Arum (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Along with the development of social media, twitter is one of the social media that becomes a place to exchange information and interact with each other. Currently, autobase accounts are often used by users to find information on certain topics. One of these autobase accounts is @ohmybeautybank which discusses topics around beauty such as make up, skincare, and also outfits. The purpose of this study is to determine whether there is an effect of exposure to twitter social media @ohmybeautybank on the consumptive behavior of followers as evidenced by the uses and effects theory. This research uses quantitative methods, the sample was taken by purposive sampling method using the slovin formula as many as 100 of the 1,467,875 followers of the @ohmybeautybank account. Data collection techniques using questionnaires and literature studies. The results of the analysis in this study can be concluded that Social Media Exposure on Twitter @ohmybeautybank has a significant influence on Followers' Consumptive Behavior as seen from the results of the t test where the tcount> ttable value (8.882> 1.660) with sig. 0.000 and an r square value of 44.6% while the remaining 55.4% is influenced by other factors not examined in this study.